College physics - Abastillas, Vivencio N., Jr.; Jose F. Aspiralla;Melencio S. Magno;Arturo L. Palisoc;Segundo V. Roxas (Quezon Avenue, Quezon City Philippines : Phoenix Publishing House, Inc., 1994)
The original text has been reorganized and rewritten with emphasis on principles and problems to provide deeper treatment and a deductive approach in a clear and simple manner. The general level of most chapters has been retained. All endeavors were done to present the concepts and principle of physics in a clear, simple and mature manner. Due to the intricacies of printing and to the large number of bits of information in the text, errors are bound to occur in a book such as this. Feedback from readers will therefore be appreciated.
Chapter 1.Measurements -- Chapter 2. Vectors -- Chapter 3. Statics -- Chapter 4. Rectilinear Motion -- Chapter 5. Newton's Law of Motion -- Chapter 6. Motion in a Plane -- Chapter 7. Friction -- Chapter 8. Work and Energy -- Chapter 9. Gravitation -- Chapter 10. Momentum -- Chapter 11. Rotational Motion and Rigid Bodies -- Chapter 12. Harmonic Motion -- Chapter 13. Molecular Forces -- Chapter 14. Fluids at Rest -- Chapter 15. Fluid Dynamic -- Chapter 16. Waves and Wave Motion -- Chapter 17. Sound Waves- Acoustics -- Chapter 18. Temperature -- Chapter 19. Heat and the Laws of Thermodynamics -- Chapter 20. Kinetic Theory of Gases -- Chapter 21.Electricity at Rest -- Chapter 22. Current and Resistance -- Chapter 23. Simple Electric Circuits -- Chapter 24. Electrical Energy -- Chapter 25. Electrochemistry -- Chapter 26. Capacitance -- Chapter 27. Magnetism -- Chapter 28. Magnetic Fields of an Electric Current -- Chapter 29. The Magnetic Circuit -- Chapter 30. Induced Electromotive Force -- Chapter 31. Inductance -- Chapter 32. Alternating Current -- Chapter 33. Nature and Behavior of Light -- Chapter 34. Reflection of Light -- Chapter 35. Refraction of Light -- Chapter 36. Optical Instrument -- Chapter 37. Interference and Diffraction -- Chapter 38. Polarization -- Chapter 39. The Special Theory of Relativity -- Chapter 40. Quantum Theory -- Chapter 41. The Atom -- Chapter 42. Nuclear Physics -- Chapter 43. Solid State, Semiconductors and Lasers -- Chapter 44. The Elementary Particles of Physics .
Includes index.
Keywords: PHYSICS